New genus and new species of the subfamily Metrodorinae from China (Orthoptera: Tetrigidae) - Lu, Xiang-Yi; Deng, Wei-An (Zootaxa, 2021)
The genus Concavetettix Deng, gen. nov. (type species: Concavetettix yunnanensis Deng, sp. nov.) is described from Daweishan, Pingbian County, Yunnan Province, China. The genus Macromotettix Günther, 1939 is reviewed. Three new species of the genus, M. microptera Deng, sp. nov., M. zhengi Deng, sp. nov. and M. brachyptera Deng, sp. nov. are described with detailed illustrations of external morphology. One new name is proposed: Macromotettix napoensis Deng, nom. nov.. Additionally, an updated key to species of the genus Macromotettix is given.